Shielding privacy: a technique of extenuating composition attacks in various independent data publication - Faruq, Md. Omar; Walid, Md. Abul Ala; Baowaly, Mrinal Kanti; Devnath, Maloy Kumar; Ejaz, Md. Sabbir; Barman, Pronob Kumar; Sattar, A H M Sarowar (Bulletin of Electrical Engineering and Informatics, 2024)
Protecting personal information from unauthorized access is a critical concern for individuals. However, the accumulation of confidential information by various organizations, such as banks and hospitals, for regular communication creates a potential vulnerability. If an individual visits two hospitals and both facilities independently release the individual's gathered data, a malicious adversary could potentially deduce confidential information through a composition attack. Therefore, developing methods that protect individuals from composition attacks is crucial. According to the size of the dataset and the percentage of overlapping persons, our study examines the effectiveness of composition attacks. We propose a knowledge domain-based design to mitigate successful composition attacks, which has shown promising results in reducing such attacks and compared to existing studies based on the k-anonymity and l-diversity models. Our approach leverages a knowledge domain to reduce the likelihood of data breaches, demonstrating the effectiveness of our method in protecting individuals' privacy and preventing unauthorized access to sensitive information. Finally, the effects of data utility on the diverse data set have been measured.